High impact of sleeping problems on quality of life in transgender individuals: A cross-sectional multicenter study - Auer, Matthias K.; Liedl, Anita; Fuss, Johannes; Nieder, Timo; Briken, Peer; Stalla, Guenter K.; Hildebrandt, Thomas; Biedermann, Sarah V.; Sievers, Caroline (PLoS ONE, 2017)
INTRODUCTION: Studies in the general population suggest that determinants of QoL are often sex-dependent. Sex-dependent analyses of QoL in transgender populations have not been performed so far. AIM: To identify sex-specific and potentially modifiable determinants of QoL in transgender patients. METHODS: In this cross-sectional multicentre study including 82 transwomen (TW) and 72 transmen (TM) at different treatment stages, we investigated potential determinants for QoL focusing on the impact of mood (BDI, STAI-X), sleep quality (PSQI), chronic pain (GPQ), body image (FBeK) and social support (SSS). MAIN OUTCOME MEASURE: Health-related quality of life measured with the Short Form (36) Health Survey (SF-36). RESULTS: The age-adjusted SF-36 total score and its subscales did not significantly differ between TM and TW. Using a multivariate regression analysis approach, we identified common but also sex-dependent determinants for QoL (Adjusted R2 = 0.228; 0.650 respectively). Accounting for general characteristics such as age, BMI and treatment status, sleep quality according to the PSQI was an independent and strong determinant of QoL in both sexes (β = -0.451, p = 0.003 TM; β = -0.320; p = 0.0029 TW). Chronic pain was a significant independent predictor of QoL in TM (β = -0.298; p = 0.042) but not in TW. In contrast, anxiety (β = -0.451; p< 0.001) being unemployed (β = -0.206; p = 0.020) and insecurity about the own appearance (FBeK) (β = -0.261; p = 0.01) were independent predictors of QoL in TW. The rate of those reporting high sleep disturbances (PSQI ≥5) was high with 79.2% in TW and 81.2% in TM. Accordingly, age-adjusted QoL was also significantly lower in those reporting poor sleep in both sexes. CONCLUSIONS: Sleep strongly affected QoL in both genders, while other factors, like pain and body image, seem to be gender specific in transgender individuals.
EVALuna2:36176